Teaching and Learning Materials in Tanzanian Secondary Schools: Challenges and Opportunities - Noel Julius Ntawigaya; Juma Kinwiko (Indonesian Educational Research Journal, 2024)
This study evaluates the effectiveness of instructional aids in secondary schools in Tanzania, focusing on their challenges and opportunities on the teaching and learning process. Employing a quantitative approach, data were collected from 100 students and 25 teachers in five randomly selected secondary schools in Mbeya. The findings highlight significant underutilization of instructional materials, with traditional tools dominating and modern technological aids largely neglected due to limited resources, inadequate classroom conditions, and insufficient teacher training. The study underscores the transformative potential of instructional aids in enhancing memory retention, concept comprehension, and student engagement. It calls for increased investment in modern instructional resources, targeted teacher training, and improved classroom infrastructure to bridge the gaps and optimize educational outcomes. These findings contribute to academic discourse on resource optimization in education and inform policies aimed at improving instructional practices in Tanzanian secondary schools.